Cosa vuol dire essere empatici. Il ruolo del nostro io nella comprensione dell’altro - Donise, Anna (Bollettino Filosofico, 2022)
The paper reconstructs the origin of the term “Einfühlung” (empathy), situating it within a Kantian-based subjectivist philosophy, and then shows limitations and potentialities of this theoretical model. In particular, the relevance of the fusional dimension understood as an original moment within a stratified conception of empathy will be highlighted. Such stratification allows one to think of the many ways in which the empathic relationship is declined not as alternative forms, but rather as different, strongly connected layers of a single process. The concluding goal of the paper will be to show that an authentic understanding of the other is possible only when we are able to understand ourselves (by separating ourselves from him or her); but at the same time, we should not forget that the process of constructing our identity originates from a fusional or unipathic dimension (Einsfühlung). Keywords: Empathy, Identity, Intersubjectivity, Self, Stratified Theory of Empathy